PENGARUH SUSTAINABILITY REPORTING DAN GREEN ACCOUNTING TERHADAP KINERJA KEUANGAN (Studi Empiris: Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2022) - Annisa Widya Tsuraya; Imam Ghozali (Diponegoro Journal of Accounting, 2025)
This study aims to investigate the influence of Sustainability Reporting and Green Accounting on financial performance. The independent variables in this study are sustainability reporting, projected through 91 indicators of the GRI G4 index, and green accounting, projected through the PROPER rating. Financial performance, proxied by Return on Assets (ROA), serves as the dependent variable. In addition, this study also uses firm size and leverage as control variables.The study employs secondary data obtained from the annual financial statements and sustainability reports of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019 – 2022 period. The sample was selected using a purposive sampling method, resulting in 42 observational data points. This research uses a quantitative method with a multiple linear regression approach.The result show that sustainability reporting has a negative and significant effect on financial performance, while green accounting has a negative and significant effect on financial performance.